Correlation of serum apolipoprotein B with the Framingham Risk Score among a group of Iraqi subjects: a cross-sectional study - Israa Nather Ahmed; Fatimatuzzahra’ Abd Aziz; Raid Dhia Hashim (PeerJ)
Background Apolipoprotein B (apoB) is the primary structural protein in low-density lipoprotein (LDL) and plays a crucial role in atherogenesis. The Framingham Risk Score (FRS) is a widely used tool for assessing cardiovascular disease (CVD) risk. However, the correlation between apoB and FRS in Iraqi individuals remains underexplored. Objectives This study aims to evaluate the association between serum apoB levels and FRS, establishing its potential utility as a predictive biomarker for coronary artery disease (CAD) risk. Methods A cross-sectional study was conducted on 201 individuals aged ≥30 years attending a clinical laboratory in Baghdad between November 2022 and October 2023. Serum apoB and lipid profiles were measured, and FRS was calculated for all participants. Correlation analysis between apoB and FRS was performed using Spearman’s test, while group comparisons were conducted via Kruskal–Wallis and Mann–Whitney tests. The predictive performance of apoB for high FRS was assessed using receiver operating characteristic (ROC) analysis, determining an optimal cutoff value. Results The median age of participants was 48 years, with males constituting 51.2% of the cohort. Median apoB and FRS values were 130 mg/dL and 4, respectively. A strong positive correlation was observed between serum apoB and FRS (R = 0.8, P = 0.0001). ROC analysis identified a cutoff value of 97.75 mg/dL for apoB in predicting high CAD risk. Conclusions These findings suggest that apoB may serve as a reliable biomarker for CAD risk assessment in the Iraqi population, where its predictive value has been underexplored. The identified cutoff value (97.75 mg/dL) highlights its potential role in refining risk stratification beyond traditional lipid markers. Further prospective studies are needed to validate these findings and assess their clinical impact.